Mitochondrial Dysfunction in Neural Injury - Zhao, Xiu-Yun; Lu, Mei-Hong; Yuan, De-Juan; Xu, De-En; Yao, Pei-Pei; Ji, Wen-Li; Chen, Hong; Liu, Wen-Long; Yan, Chen-Xiao; Xia, Yi-Yuan; Li, Shao; Tao, Jin; et al. (Frontiers in Neuroscience, 2019)
Mitochondria are the double membrane organelles providing most of energy for the cells. In addition, mitochondria also play essential roles in various cellular biological processes such as calcium signaling, apoptosis, ROS generation, cell growth and cell cycle etc. Mitochondrial dysfunction is observed in various neurological disorders which harbor acute and chronic neural injury such as neurodegenerative diseases and ischemia, hypoxia-induced brain injury. In this review, we describe how mitochondrial dysfunction contributes to the pathogenesis of neurological disorders which manifest chronic or acute neural injury.